À l’Est de l’Europe, quoi de neuf en matière de réformes territoriales ? Réflexions à partir de la régionalisation en Bulgarie - Emmanuelle Boulineau (EchoGéo)
By analyzing regionalization processes in Bulgaria since 1989, the paper aims at interpreting the territorial reforms in Central and Eastern Europe after the fall of the Iron Curtain and, the EU integration during the 2004-2007 Enlargement period. It explains the post-socialist reforms in Bulgaria and links them with the regional disparities. It shows that two types of regionalization both exist; one oriented towards administrative functions, the other based on territorial competitiveness. By comparing with the Central and Eastern Europe, the paper explores their ambiguities. It concludes with expected challenges concerning the territorial reform in Bulgaria.